Xerophthalmia due to vitamin A deficiency following Frey's procedure for chronic calcific pancreatitis. Issue 5 (24th May 2021) - Sharma, Supriya; Murthy, Somasheila I; Bhate, Manjushree; Rathi, Varsha
Abstract : We report a rare presentation of xerophthalmia due to partial pancreatic exocrine insufficiency following Frey's surgery (pancreatic resection) in a 12-year-old girl. The child had undergone this surgery for chronic calcific pancreatitis 3 years before and presented with ocular irritation and decreased vision of 3 months duration. Ocular examination showed severe conjunctival and corneal xerosis. Her serum retinol levels and 25-hydroxyvitamin D were tested and were extremely low. The condition rapidly reversed following high-dose replacement therapy with vitamin A and D. This case highlights the importance of continuous enzyme replacement therapy as well as dietary modification and nutritional supplement therapy and monitoring of ocular symptoms in post-pancreatic surgery.